2020
DOI: 10.3390/ijms21093160
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Two Klebsiella pneumoniae Phages Encoding Divergent Depolymerases

Abstract: The emergence of multidrug-resistant bacteria is a major global health concern. The search for new therapies has brought bacteriophages into the spotlight, and new phages are being described as possible therapeutic agents. Among the bacteria that are most extensively resistant to current antibiotics is Klebsiella pneumoniae, whose hypervariable extracellular capsule makes treatment particularly difficult. Here, we describe two new K. pneumoniae phages, πVLC5 and πVLC6, isolated from environmental samples. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
0
34
1
Order By: Relevance
“…Morphology of plaques from Ganges water showed a halo around the clear zone, which might indicate depolymerase activity of KpG that could target the capsule of the strain (Fig. 1 ) (Domingo-Calap et al 2020 ). The phage displayed stability at pH: 7.0, 9.0, 11.0 with a survival rate of 99%, 98% and 60% respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphology of plaques from Ganges water showed a halo around the clear zone, which might indicate depolymerase activity of KpG that could target the capsule of the strain (Fig. 1 ) (Domingo-Calap et al 2020 ). The phage displayed stability at pH: 7.0, 9.0, 11.0 with a survival rate of 99%, 98% and 60% respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our observation, another report showed that four lytic phages, belonging to the family Podoviridae , infecting K. pneumoniae capsular type K22, were isolated from environmental samples. They possessed narrow infectivity only against a K. pneumoniae clinical isolates with K22 capsular type (Domingo-Calap et al 2020 ). Moreover, the plaque morphology showed a halo around the lysis area, implying presence of depolymerase that lyses the capsule (Domingo-Calap et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, the host range of other Acinetobacter infecting phages varied between 2-68%, and in some reports, newly isolated phages infect only their propagation host [11,14,20]. Additionally, the host range of acinetobacter-infecting podoviruses mainly depended on pectate lyase depolymerase domains located on the tail fibers [16,[21][22][23][24]. It can be presumed that isolation and characterization of naturally occurring Acinetobacter phages is important and puts novel insights into their biology.…”
Section: Discussionmentioning
confidence: 99%
“…The number of RBPs with depolymerase activity per phage is highly variable. Phage KP36 produces a single RBP and is only active against serotype K63, corresponding to the substrate specificity of its RBP (8,16), whereas other phages (e.g., KP32, K5-2, K5-4, and UK64-1) encode more RBPs with depolymerase activity, recognizing a corresponding number of capsular serotypes (6,7,9,10,17) and resulting in a broader host spectrum. A similar relationship has also been described for Escherichia coli and Salmonella phages (18)(19)(20).…”
mentioning
confidence: 99%